PEMBENTUKAN DAN PENATAAN ORGANISASI PERANGKAT DAERAH - Suaib, Suaib (Katalogis, 2017)
This writing wants to know what the purpose of the establishment of regional organizations as well as whether the factors that hinder the arrangement of regional organizations, through the method of normative and regulatory approaches law (Statute Approach) and the conceptual approach (Conceptual Approach), found things as follows; 1). The purpose of establishing regional organizations have three fundamental objectives, namely; (1) To Achieve Objectives Granting autonomy; (2) To carry out certain government affairs; (3) To carry out public services; 2) Structuring regional organizations is one of the steps to set up a system that Local Government system. Therefore, the arrangement of regional organizations not in spite of the obstacles faced, namely; (1) Aspects of human resources; (2) the financial aspects; (3) Changes in the legislation.